Real-Time Geophysical Monitoring of Particle Size Distribution During Volcanic Explosions at Stromboli Volcano (Italy) - Pioli, Laura; Harris, Andrew J. L. (Frontiers in Earth Science, 2019)
Of all the key parameters needed to inform forecast models, real-time tracking particle size distribution (PSD) of pyroclasts leaving the vent coupled with plume modeling has probably the highest potential for effective management of volcanic crises. This paper presents an algorithm capable of providing syn-emission horizontal size and velocity of particles in real time, converted in mass discharge rates, and its evolution during an explosion, using thermal infrared videos. We present data on explosions that occurred at the SW crater of Stromboli volcano (Italy) in 2012. PSDs and mass eruption rate data, collected at frequencies of 40 Hz, are then coupled with particle and gas speed data collected with traditional image analysis techniques. The dataset is used to quantify the dynamics of the explosions and magma fragmentation. We find that explosive evacuation of magma from a Strombolian conduit during a single explosion proceeds at a constant rate while the explosive dynamics are marked by a pattern that includes an initial transient and short phase until the system stabilizes at equilibrium. These stationary conditions dominate the emission. All explosions begin with a gas jet (onset phase), with maximum recorded vertical velocities above 150 m/s. These high velocities are for small particles carried by the faster-moving gas or pressure wave, and larger particles typically have slower velocities. The gas jets are followed by a particle-loaded plume. The particles increase in number until the explosion dynamics become almost constant (in the stationary phase). Mass eruption rate is either stable or increases during the onset to become stable in the stationary phase. The shearing at the interface between the magma and the gas jets controls fragmentation dynamics and particles sizes. Quantification of the Reynolds and Weber numbers suggest that the fragmentation regime changes during an explosion to affect particle shape. This method relates to lapilli and bomb-dominated emissions associated with low energy primary fragmentation. In general terms, its applicability is limited by the size of individual pixels recorded by the camera, which depends on the detector, the recording distance and the optical system, particle temperature, which has to be significantly higher than the background.